KINERJA TRANSPORTER TERHADAP PENCAPAIAN ON TIME DELIVERY PADA PERUSAHAAN LOGISTIK - Nasrullah Nasrullah; Anggun Alami; Okin Ringan Purba (Institut Transportasi dan Logistik Trisakti, 2017)
PT Inti Dinamika Logitama Indonesia is a company engaged in loading and unloading cargo services as well as freight forwarding. The main issue studied in this research is how big the effect of transporter performance to the achievement of on-time delivery at PT Inti Dinamika Logitama Indonesia is. The objective of this study is to find out how big the effect of transporter performance to the achievement of on-time delivery is using two methods. Data were collected by (1) Field research, in form of interviews and library research; and (2) Correlation analyses, coefficient determinant, and hypothesis testing. The result of the analysis and discussion shows that there is a low yet definite effect between the transporter performance to the achievement of on-time delivery with multiple linear regression equation Y = 35, 90 + 0,145X. It means, if there is a change in transporter performance data, it will affect the achievement of on-time delivery performance. The correlation coefficient equals to 0.3460.769, which means there is a low effect between X and Y. The coefficient determinant shows that the contribution of employees’ performance towards the achievement of on-time delivery equals to 11.97% while 88.03% comes from other factors. Hypothesis test also shows that F stat > F table (2,272 > 1,686), then Ho is rejected and H1 is accepted. It shows that there is a significant effect between the employees performance to the achievement of on-time delivery.